Princess Diary - Krantz, Judith (New York Bantam, 1981)
Born the daughter of a Russian prince and an American movie goddess, Daisy lived in a world of aristocrats and wealth. Then one day the fairy tale ended and Daisy had to start again, with nothing.
Keywords: Princesses -- Models (Persons) -- Orphans